The Crucial Role of Language in the Implementation of Medical Chatbots and Virtual Assistants in Medicine - Ablaqulova Parizoda Akbar qizi; Esanboyeva Mushtariy Alijon qizi (Genius Journals, 2024)
The writing emphasizes the crucial role of language processing capabilities in the implementation of medical chatbots and virtual assistants in medicine. It highlights how these capabilities enhance communication with patients, enable accurate understanding of medical knowledge and terminology, and facilitate language understanding and intent recognition. The paper also emphasizes the importance of multilingual support, cultural sensitivity, and streamlining documentation and record-keeping. Furthermore, it discusses how language processing enhances diagnostic capabilities, enables contextual understanding, and supports emotional well-being and patient education. The paper concludes by highlighting the value of continuous learning and improvement, as well as the support provided to healthcare professionals. Overall, the writing underscores the transformative potential of language-enabled systems in revolutionizing healthcare delivery and improving patient outcomes
Keywords: Effective communication; Natural Language Processing; complex medical concepts